TRANSLASI BUNYI KE TEKS: MODEL PROJECT-BASED LEARNING DALAM PEMBELAJARAN PENULISAN KARYA SENI DI PROGRAM STUDI ANGKLUNG DAN MUSIK BAMBU - Ega Fausta; Dyah Murwaningrum (Keteg : Jurnal Pengetahuan, Pemikiran dan Kajian Tentang Bunyi, 2025)
Students of the Angklung and Bamboo Music Study Program often face challenges in transforming their musical practice excellence into structured academic writing for their final projects. This article identifies a significant gap between practical skills and academic literacy. Based on data collected through literature review, Likert-scale surveys, and interviews with lecturers, the main challenges lie in students’ limited academic literacy and difficulties in linking theory with artistic practice. Although the Art Writing course is considered highly relevant (score 4.6) to the final project, students’ conceptual understanding remains moderate (3.8). The findings highlight an urgent need for cross-course integration (score 4.7). As a strategy to bridge this gap, the study recommends implementing a Project-Based Learning (PjBL) model within an Outcome-Based Education (OBE) framework. Combined with curriculum improvement that strengthens integration, this approach aims to position academic writing not as a separate activity but as an integral part of the creative process of sound-making, thereby enhancing the holistic quality of students’ final projects. Keywords: Sound studies; Art writing; Academic literacy; Angklung and bamboo music; Project-Based Learning;